THE PRINCIPLE OF GENDER EQUALITY UNDER FAMILY LAW: EXPERIENCE OF FOREIGN COUNTRIES AND UKRAINE - Kmetyk, Khrystyna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to study the principle of gender equality in family law, specifically the experience of foreign countries and its impact on the development of family legal relations in Ukraine. The focus is on the importance of ensuring the equal rights and opportunities for women and men in the context of family legislation, as well as the challenges that arise when implementing the gender equality. Research methods: the article uses a comparative-legal method to analyse international experience in family law and the principles of gender equality. It also applies methods of analysing legislative acts and international agreements related to gender equality to examine how different countries implement this principle in their legal environment. Results: the article points on the importance of implementing the principle of gender equality in family law to achieve social justice and sustainable development of society. An analysis of foreign legislations (France, Sweden, Norway, Iceland, Canada, etc.) demonstrates various approaches to ensuring the equal rights for women and men in family relations, including the equality in marriage, the equal parental rights and rights to alimony. In Ukraine, there is also a gradual integration of European standards, although there are certain problems, including the cultural and social stereotypes that may complicate this process. Discussion: the article highlights that, although Ukraine has a legal framework guaranteeing gender equality, its implementation in practice faces barriers such as stereotypes and limited access to legal information. Furthermore, it emphasizes a need to adapt national legislation to modern requirements regarding gender equality and a necessity to consider cultural and social features that may influence the formation of gender roles in the family. The article also suggests developing the concept for the development of Ukraine’s family legislation based on the analysis of international experience and internal trends.